2004
DOI: 10.1128/jvi.78.18.9675-9688.2004
|View full text |Cite
|
Sign up to set email alerts
|

The Conserved Carboxy Terminus of the Capsid Domain of Human Immunodeficiency Virus Type 1 Gag Protein Is Important for Virion Assembly and Release

Abstract: The retroviral Gag precursor plays an important role in the assembly of virion particles. The capsid (CA) protein of the Gag molecule makes a major contribution to this process. In the crystal structure of the free CA protein of the human immunodeficiency virus type 1 (HIV-1), 11 residues of the C terminus were found to be unstructured, and to date no information exists on the structure of these residues in the context of the Gag precursor molecule. We performed phylogenetic analysis and demonstrated a high de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
59
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 58 publications
(68 citation statements)
references
References 92 publications
7
59
0
Order By: Relevance
“…As the result of evolution, some sites remain conserved due to their functional significance, while others are highly variable [41]. Such variability is likely to be advantageous to the organism [42].…”
Section: Synteny Analysis Of the P2x Genes In Vertebratesmentioning
confidence: 99%
See 1 more Smart Citation
“…As the result of evolution, some sites remain conserved due to their functional significance, while others are highly variable [41]. Such variability is likely to be advantageous to the organism [42].…”
Section: Synteny Analysis Of the P2x Genes In Vertebratesmentioning
confidence: 99%
“…Analyzing and detecting amino acid site under selective pressure is critical for understanding protein function and structure [41]. Past studies have shown that duplicated genes undergo three different kinds of destines after duplication events: neo-functionalization (gain new functions), sub-functionalization (subdivide the functions), and pseudogenization (loss of function) [65][66][67].…”
Section: Variable Selective Pressures Among Amino Acid Sites Of the P2xmentioning
confidence: 99%
“…We adopted the protocol of Melamed et al [39] to analyze the cytoplasmic Gag complex. Briefly, cells were rinsed twice with PBS, pelleted and resuspended in 1 ml TEN buffer containing Complete protease inhibitor cocktail followed by homogenization as described above.…”
Section: Velocity Sedimentation Analysis Of Cytoplasmic Gag Proteinsmentioning
confidence: 99%
“…These data suggest that the C-terminal one-third of the gag sequence contains domains necessary for Gag assembly and release. There is an increasing amount of published data on mapping of the domains responsible for Gag-Gag interactions, and such studies have implicated the C-terminal CA and the downstream NC [36][37][38][39]. In particular, it has been shown that deletion or some substitution mutations in MHR markedly reduce virus particle production [27,38,40].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation